Professions and Professionalism Ä±n a Hosting Setting of Georgia - Gerzmava, Otar; Turmanidze, Guguli; Lomtadze, Lili; Tegetashvili, Ana; Gerzmava, Nino (European Scientific Journal, ESJ, 2017)
The trust that society places in the professional is rooted in the professed commitment made by the professional, and it takes life in the service that is provided. That service is in the care provided to the patient, a care rooted in the expertise acquired by years of study and experience. But the increasing complexity of medical care, the variety of tools available for diagnosis, the wide range of specialties in care, the diminished expectations of the times when a physician is available makes it clear that medical care is a team effort that the service of the medical professions is provided by a variety of interdependent practitioners. This increasing complexity requires that professional autonomy cannot exist in isolation, and suggests that we must look a bit more carefully at what we mean by service.